"Are you good at dating?" - Liselott Aarsand (Educare)
Within various everyday practices there is a tendency to talk about, categorise and deal with what happens through discourses of learning. Popular culture reveals clear examples of how learning vocabularies and repertoires are used across activities like cooking, parenting, private finances and dating to attain what is displayed as better practice. Drawing upon perspectives highlighting the social dynamics in encounters, I have explored the issue of dating portrayed in a lifestyle television show through the research question: How is learning made relevant in talk on dating practices, and in what ways are subjectivities shaped through such discursive work? A close-up analysis of talk sequences indicates how the interlocutors use discursive resources to frame what happens as a learning event claiming pedagogical subjectivities, relationships and activities. Dating evolves around knowledgeability defining the novice positioning with the need to prepare oneself and cultivate adequate skills through practising. Addressing and promoting knowledgeability, practising and skilfulness as the key to success can empower adults, however, in establishing an aura of normalcy – a “natural” way of operating in daily life – this also becomes a powerful tool for governing oneself and others. A main concern is therefore to critically discuss how the talkative business of learning unfolds in practices beyond formal education.